Analysis and Synthesis of Alternative Solutions to Environmental Problems Associated with Large-scale Projects - Davidovich, Gelrud Yakov; Jianan, Cui; Bekun, Festus Victor (International Journal of Energy Economics and Policy, 2023)
In this study the environmental problems in the large-scale project called "Ecology of the Angaro-Yenisei region" are addressed. A description of various approaches to assess the program of conservation and restoration of the Yenisei as the basis of the ecological potential of the Angaro-Yenisei region is presented. A justification is given for taking into account the uncertainty in such an assessment. The present study suggests three stages of assessment for different levels, macro-, meso- and microlevel. The estimates of the previous assessment level are the initial information for the lower level, which allows a gradually reduction of the degree of uncertainty. At the first stage, the goals of the program were developed and ranked by expert assessment methods. The second stage consisted in analyzing the National Project called "Ecology of Russia," composed of 11 interconnected federal projects. A mathematical model of the problem of optimal project management in conditions of uncertainty is presented. At the third stage, a hybrid model of assessing a large ecological project from the logical-descriptive model created at the first stage and the mathematical model of stage 2 is considered. Similar models, in the creation of which the authors took part, were used in the assessment of large-scale railway projects. More specifically, with the help of one of them, an analysis of the development of the Asian part of the Russian Federation was carried out by the Siberian branch of the Russian Academy of Sciences. In conclusion, the need of the use of mathematical methods at various stages of assessing large-scale environmental projects from their initiation to implementation is justified